Experimental determination of metals generated during the thermal failure of lithium ion batteries. (3rd January 2023) - Buston, Jonathan E. H.; Gill, Jason; Lisseman, Rebecca; Morton, Jackie; Musgrove, Darren; Williams, Rhiannon C. E.
Abstract : This work describes the deliberate failure of lithium-ion cells, and subsequent analysis of both the smoke and near field residue for the metals commonly found in battery cathodes. Abstract : Lithium ion cells, although near ubiquitous as a portable power source in today's society, have rare, but well documented failure pathways which generate gas, fumes and smoke, and often result in fire. Whilst the composition of the gas has been subject to much analysis, far fewer reports have focussed on the nature of any solid materials released. This work describes the causing to fail (by applying an external heat source) of a range of commercially available and widely used cells. Samples of both the smoke generated during the failure, and the residues left surrounding the cell after failure, were analysed for metal content by ICP-AES. These showed that all samples contained the key metals expected to be in cell cathodes (nickel, manganese, cobalt and aluminium) in not dissimilar ratios. However, the ratio of these elements differed from cell to cell, as the cathode varied.